A Group Independent Study Using a Client-Based Promotional Plan Project: Design and Assessment. Issue 3 (2nd September 2018) - Preston, Teresa
Abstract : Client-based group projects (CBGP) enhance learning through processes of experience and application along with peer-based learning, while independent learning may induce a more active learning role and increased level of self-responsibility. The descriptive case in this article reviews the implementation of a group independent study where project completion is to finish a client's promotional plan for an Integrated Marketing Communications (IMC) course. This case describes the course's inputs and processes to propose that integrating learning inputs and processes from CBGP work and independent study may enhance learning outcomes. Learning effectiveness and work performance are reviewed with lessons learned and directions for future research.